Electrochemical formation of molybdenum phosphate on a pencil graphite electrode and its potential application for the detection of phosphate ions - Arvas, Melih Besir; Gursu, Hurmus; Gencten, Metin; Sahin, Yucel (ROYAL SOC CHEMISTRY, 2018)
The one-step electrochemical preparation of a molybdenum phosphate coated pencil graphite electrode was achieved in phosphoric acid and lithium molybdate solutions at room temperature. The electrodes were prepared by cycling the potential between -1.0 V and +1.9 V (vs. Ag/AgCl) in one-step. The surface morphology of the electrodes was investigated by scanning electron microscopic analysis. The chemical structure of the surface was determined with X-ray photoelectron spectroscopy and X-ray diffraction spectroscopy. The electrochemical behaviors of the electrodes were investigated by cyclic voltammetry and electrochemical impedance spectroscopy. The prepared electrodes were used for the detection of phosphate in soil samples. The molybdenum phosphate modified pencil graphite electrode showed excellent sensitivity for phosphate analysis with a relatively low limit of detection and a limit of quantification of 1.25 x 10(-6) M and 4.15 x 10(-6) M, respectively. The novel sensor described herein is economical, easy and environmentally-friendly to prepare, and can be used in many environmental analyses for the detection of phosphate with high sensitivity.
Keywords: FACILE SYNTHESIS; POLYPYRROLE; PHOSPHORUS; PERFORMANCE; BIOSENSOR; CATALYST; BATTERY; SYSTEM; FILMS; NANOPARTICLES; Chemistry; Food Science & Technology; Spectroscopy